Interprofessional Learning Through Shadowing in Rehabilitations Department: A Qualitative Study of the Student´s Placement in Hospital Setting - Synnove Hofseth Almas; Halvard Nilsen; Randi Spjutoy; Froydis Vasset (European Scientific Journal, ESJ, 2017)
Interprofessional collaborative learning (IPL) is a requirement in health and social education, primary in student placements. This study explored IPL as shadowing with seven participants at a department of physical medicine and rehabilitation in a hospital. Seven participants were divided into two groups (n=3; n=4) when caring for two patients. Both groups wrote a rehabilitation plan together with the patients. In a submitted template, the students reflected on roles and responsibilities of health care professionals. To examine how the informants expressed their experiences of IPL, focus group interviews were conducted with each group and transcribed. The focus group transcripts, together with submitted templates, were then analysed using Giorgis’ model of content analysis. All informants expressed that IPL led to acquired knowledge about each other’s responsibilities in healthcare. Participants were aware of differences and similarities between their responsibilities. They reported that leadership and communication are prerequisites for collaborative practice.